2019
DOI: 10.1007/s40430-019-2140-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the flow distribution in parallel micro-channels with a triangular manifold

Abstract: Flow distribution and pressure drop in parallel micro-channels are two effective parameters on the performance of different devices. These two parameters are affected by different factors, such as the manifold geometry, channels geometry, flow rate and fluid direction of inlet flow. In the present work, the structure of the inlet manifold (the triangular geometry, with straight and curved walls) has been studied as the main subject. However, the effect of the flow rate (as the Reynolds number) and fluid direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The literature on microscale devices (both experimental and CFD studies) has been discussed in detail in Section 2.1. Several significant strategies to address the issue of maldistribution through numerical/analytical techniques for different geometrical configurations include 1) analytical/discrete models preferred as compared to CFD by researchers (Devia et al, 2015;Wang and Wang, 2015;Tomor and Kristóf, 2016) for U-and Z-type manifolds, 2) incorporation of internals like distributors for manifolds with central inlets and outlets (Zhao et al, 2017;Gilmore et al, 2021), 3a) optimization of geometric parameters like (b) inlet diameter to individual tube ratios (Hadad et al, 2020); shape of the inlet (like triangular inlets) (Zoljalali and Omidbakhsh Amiri, 2020); and (c) other geometrical parameters (Zhuang et al, 2020;Ghasabehi et al, 2021), 4) header designs with multistage topologies (Ju et al, 2018;Zeng et al, 2018), and 5) number of flow inlets and outlets (Lim et al, 2018). Experimental works to study maldistribution include the following: 1) optimizing outlet diameters for bifurcation manifolds (Zhuang et al, 2019); 2) geometry optimization by measuring current as a function of flow (Ji et al, 2019).…”
Section: Literature Review Summarymentioning
confidence: 99%
“…The literature on microscale devices (both experimental and CFD studies) has been discussed in detail in Section 2.1. Several significant strategies to address the issue of maldistribution through numerical/analytical techniques for different geometrical configurations include 1) analytical/discrete models preferred as compared to CFD by researchers (Devia et al, 2015;Wang and Wang, 2015;Tomor and Kristóf, 2016) for U-and Z-type manifolds, 2) incorporation of internals like distributors for manifolds with central inlets and outlets (Zhao et al, 2017;Gilmore et al, 2021), 3a) optimization of geometric parameters like (b) inlet diameter to individual tube ratios (Hadad et al, 2020); shape of the inlet (like triangular inlets) (Zoljalali and Omidbakhsh Amiri, 2020); and (c) other geometrical parameters (Zhuang et al, 2020;Ghasabehi et al, 2021), 4) header designs with multistage topologies (Ju et al, 2018;Zeng et al, 2018), and 5) number of flow inlets and outlets (Lim et al, 2018). Experimental works to study maldistribution include the following: 1) optimizing outlet diameters for bifurcation manifolds (Zhuang et al, 2019); 2) geometry optimization by measuring current as a function of flow (Ji et al, 2019).…”
Section: Literature Review Summarymentioning
confidence: 99%
“…They found that A30 with convex shape and two outlets have the least dead volume space. Zoljalali1 and Amiri 17 investigated the triangular shape of manifold design with channel width and depth along with number of channels to understand the flow distribution and pressure drop in microchannels. They found that triangular manifold of equilateral triangular shape with concave wall structure has better flow uniformity among other considered shapes in their study.…”
Section: Introductionmentioning
confidence: 99%